Good Governance Bisnis Syariah Terhadap Islamicity Financial Performance Index Bank Umum Syariah - Widiastuti, Ayu; Wulan, Mulyaning (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
This study describes the effect of Good Sharia Business Governance implementation of financial performance as measured by Islamicity Financial Performance Index. The indicator used to explain Good Sharia Business Governance in this study based on the guidelines for its application issued by the KNKG that composed of commissioners, supervisory sharia board (SSB), directors and other information. The method of this study ismultinomial logistic regression. The sample used is the Islamic Banks that registered in the BI during the observation period 2011-2015. To determine the sample selection method used purposive sampling. With this method, the obtained 8 Islamic Banks to be used as a sample in this study. The results of this study indicate that simultaneously affect the Islamicity Financial Performance Index. Partially commissioners have influence while DPS, directors, and other information have no effect on Islamicity Financial Performance Index.